Implementasi Shibori Di Indonesia - SIti Maziyah; Sri Indrahti; Alamsyah Alamsyah (Diponegoro University, 2019)
(Title: Shibori Implementation in Indonesia) Shibori is a technique for making batik-like cloth motifs carried out in Japan. Lately, this technique has been favored by many Indonesians because of its simpler technique and faster production than batik making. Actually this technique is similar to batik, which is doing a color barrier to create a motif on the fabric. If in batik the barrier device used is wax, then the shibori used can be from various tools such as rubber, yarn, clothespin, and so on. Based on a search on the culture of making traditional fabric motifs in Indonesia, it turns out that the shibori technique has also been carried out by fabric artisans in Indonesia. What is the implementation of shibori in Indonesia like? By using literature studies from various writings relating to making fabric motifs, finally some shibori techniques can be investigated that have been carried out by traditional fabric artisans in Indonesia.